Nuclear Elongation Factor-1 Gene A Molecular Marker for Iranian Sandfly Identification - P Parvizi; M Assmar (Tehran University of Medical Sciences, 2007)
Background: Elongation factor-1, a conserved nuclear protein coding gene was used to identify Iranian sandfly species. The phlebotomine sandfies are the vectors of the parasitic protozoan Leishmania, the causative agents of leishmaniasis, in Iran. Methods: Seven sets of primers were tried. PCR amplification of elongation factor-1 was successfully achieved for all 14 species of Iranian sandflies that we caught, but different primers had to be used. Results: The aligned DNA sequences of 454 bp (without primers) of the gene had the most similarity to a coding region of the elongation factor-1 genes of D. melanogaster, as identified by a BLAST search of GenBank. Each Iranian species, except Phlebotomus caucasicus and P. mongolensis, had a unique combination of nucleotides, i.e. each had a diagnostic sequence. There were no diagnostic sequences for different geographical populations of the species in Iran. We found only a single copy of Ef-1 gene in most individual sandflies. However EF-1 gene was successfully amplified by PCR but, unfortunately, phylogenetic analysis showed that it might be multicopy in sandflies and so the markers could not be trusted. Conclusion: More highly polymorphic nuclear loci, like microsatellites, might be needed to distinguish morphologically indistinguishable females of the subgenus Paraphlebotomus, e.g. P. caucasiscus from P. mongolensis, in order to resolve their roles as vectors of Leishmania species in gerbils.